The Relationship between Work Attitude and Weight Load with Complaints of Low Back Pain (LBP) in Transporting Workers of Catched Fish at Fish Auction Sites (TPI) - Reni Aprinawaty Sirait; Murti Sri Dewi (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Occupational diseases are one of the diseases that can be experienced by workers in their work, which are at risk of causing occupational diseases, namely, work equipment, work environment, and the process of their work. Occupational diseases caused by work attitudes can be influenced by non-ergonomic positions and activities that are carried out incorrectly, such as the wrong position when lifting heavy loads are also the cause of low back pain.The purpose of this study is to explain the relationship between work attitude and weight with complaints of low back pain (LBP) in workers transporting the catch.This study uses a descriptive analytic method using a cross sectional design. The population in this study were all workers transporting fish catches totaling 52 workers with a sample of 34 workers who were taken using purposive sampling technique. The instrument used is a questionnaire. Data analysis was carried out univariate and bivariate using the Spearman rank test with = 0.05. The results of the analysis show that there is a relationship between work attitude and complaints of low back pain (p value = 0.000) < 0.05 and there is a relationship between the weight of the load and complaints of low back pain (p value = 0.036) < 0.05. This happens because the way of lifting when lifting weights is not right and lifting excessive loads so that it causes injury to the spine which results in low back pain. Based on the results of the research above, for workers to use tools such as hand trucks in transporting fish catches.